Criminal responsibility of civil society organizations for financial corruption crimes - Saeed, Zana Rafiq; Jabar, Chnar; Ameen, Mohamed (Journal of Legal and Political Studies, 2022)
Civil society organizations were and still represent, to a fundamental degree, one of the basic components of society, so we find it that social organization that is led by individuals towards achieving certain goals, framed according to the law in a legitimate and verifiable manner in order to achieve its goals set in its internal system, all of this is done within strictly drawn up legal frameworks , but of course, and it is the natural state of human beings that they may initiate what constitutes a violation of the law by committing certain acts that are crimes, especially crimes of financial corruption, which requires criminal responsibility, here the question arises who will bear criminal responsibility here? Is the organization as a whole? Or the person who works for her or in her name or her representative?
Keywords: criminal responsibility; civil society organizations; legal persons; financial corruption